Pengaruh Pillar 1 OECD (Unified Approach) Terhadap Pemajakan Digital Di Indonesia - Surono Surono; Vita Apriliasari (JURNAL PAJAK INDONESIA, 2022)
Pillar 1 OECD (Unified Approach) aims to reallocate taxation rights for market jurisdiction that are being eroded between USD100-240 billion per year (4-10% of Global GDP) due to the constraints of digital economy taxation for multinational enterprise (MNE). On the other side, the adoption of Pillar 1 will increase the potential for corporate income tax revenue from MNE. Jurisdictions also get challenges in the readiness of tax authorities regarding human resources and facilitating systems, as well as the readiness of domestic laws for the implementation of Pillar 1 OECD. Indonesia also plays an important role as the G20 2022 presidency to succeed the Pillar 1 OECD agreement. The research was conducted using literature study and interview methods. There are 110 MNEs covered by Pillar 1 that can increase the potential for tax revenues so as to create justice in the international tax system. For this reason, tax authorities need to prepare qualified human resources and automated information technology to save costs and maximize data collection and analysis. Domestically legal, Article 32A of the Law on the Harmonization of Tax Regulations has facilitated the implementation of Pillar 1 OECD. Implementing regulations are being prepared in the form of Government Regulations or Regulations of the Minister of Finance which are still waiting for the model rules, communtary, and annex from Pillar 1 of the OECD.